Examining Predictors of Differential Attitudes toward Reporting Sexual Assault among Incarcerated Women. Issue 2 (15th March 2023) - Smith, Wesley; Mullings, Janet; Blackburn, Ashley; Fowler, Shannon
ABSTRACT: This study examines how attitudes toward in-prison sexual assault reporting have changed over time. Further, we examine factors that influence the willingness of incarcerated women to advise reporting in-prison sexual assaults. Responses from two cross-sectional samples taken ten years apart with 814 incarcerated women are examined. Findings suggest that women surveyed in 2016 were less likely than those surveyed in 2005 to advise the immediate report of a sexual assault. Factors such as age, sexual orientation, violent offense, and perceptions of safety were significant predictors of reporting behaviors. Implications for future research and policy are discussed.